Pengaruh Partisipasi Penyusunan Anggaran Terhadap Kinerja Manajerial Pada Sekolah Menengah Negeri di Tegal - Wicaksono, Galih (Faculty of Economic and Business, 2016)
The Influence of Budgetary Participation on Managerial Performance in Stated Owned High School in TegalThis study examined the influence of budgetary participation to managerial performance through budget adequacy, organization commitment, and job relevant information as intervening variables. The population of this study is staff that budgetary participation at Public School in Tegal. The sample of this research is collected with contact person. The result of this study showed that budgetary participation has not effect to managerial performance. Other result that is shown in this study is that budgetary participation has positive effect to budget adequacy, organization commitment, and job relevant information. But, budget adequacy and job relevant information has not effect to managerial performance. Just organization commitment has positive effect to managerial performance. So, Budgetary participation has positive effect to organization commitment, and then organization commitment has positive effect to managerial performance.DOI: 10.15408/ess.v6i2.3575